EVALUATION OF PROGRAMS IN A PAUD CLASSROOM (Study on Lebong Regency SPNF (SKB) - Rerin Handayani; Turdjai Turdjai (UNIB Press, 2019)
This study aims to reveal, implement, achieve success and the obstacles that affect the success of the tiered training program at the basic level of Early Childhood Educators who have high school qualifications and SI are not the PAUD field in Lebong Regency SPNF (SKB). This research is an evaluation research using Context, Input, Process, Product. The subject of this study was a level-level tiered training participant. Data collection is done by interview method, documentation, and observation. Furthermore, the data obtained were analyzed using analysis at Lebong Regency SPNF (SKB) to obtain data validity, expert discussion, and extension of observation. The results of the study are as follows, context aspect shows the suitability between training participants' needs and participation, training parti1 cipants' experience, and environmental conditions with training program activities, input aspects indicate training participants' motivation, training participant characteristics, resource characteristics, funding, and infrastructure in the category Good, the process aspect shows the training participants' activities, learning strategies and interpersonal relationships are also in good categories. Product aspects show that all levels of basic education and training activities can be implemented well. The success of the basic level education and training program is shown by the improvement in the minimum competence of PAUD educators which includes understanding tasks and authority in assisting educators and accompanying educators. Constraints in the implementation of the training program include less than optimal cooperation, and the media and teaching aids cannot function optimally.